The Effect of Social Media Use Intensity on Student Stress Levels (A Study of Students at The Faculty of Economics and Business, Syahada Islamic University of Padangsidimpuan) - Eva Sunarti; Salsa Billa Ilda Putri Prasetya; Nasution, Ananda Saprilla; Siregar, Ihsan Mulia (Nusantara: Journal of Cultural Research, 2025)
This study aims to analyze the effect of social media usage intensity on the stress levels of students at the Faculty of Economics and Islamic Business (FEBI) UIN Syahada Padangsidimpuan. Motivated by the rapid development of social media and its potential impact on students' psychological well-being, this study uses a quantitative approach with a correlational design. A total of 60 active FEBI UIN Syahada Padangsidimpuan students in the even semester of the 2024/2025 academic year were selected using purposive sampling. Data were collected through an online questionnaire that included the Social Media Intensity Scale and the Perceived Stress Scale (PSS-10), which have been tested for validity and reliability. Data analysis used simple linear regression after the classical assumption test was fulfilled. The results showed that the intensity of social media use had a positive and significant effect on students' stress levels (B = 0.457, t = 4.115, p = 0.000 < 0.01), contributing 21.7% to the variation in stress levels (R² = 0.217). This study concludes that the higher the intensity of social media use, the higher the stress levels experienced by FEBI UIN Syahada Padangsidimpuan students. The implication of this study is the need to develop interventions and digital literacy programs that consider the psychological well-being of students in an Islamic campus environment. The limitations of this study include its cross-sectional design and limited sample size.